2022
DOI: 10.3389/fpsyg.2022.1059727
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in Uchikomi fitness test performance: Influence of warm-up protocols

Abstract: Performance is judged using a variety of methods to ensure uniformity between competitions. Uchikomi Fitness Test (UFT) could accomplished between morning qualifying and evening finals. The purpose of this study is to investigate the impact of different warm-up protocols on UFT at different times of the day in female judokas. Ten volunteer women who had been practising judo on a regular basis for more than 5 years and actively competed in international tournaments took part in this study. Judokas completed UFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a study, Chtorou et al [2] found that power output increased in male sprinters during the 30-s Wingate Anaerobic Test (WAnT) after a 10-min warm-up with and without music. It has been reported in many exercises in the literature that methods such as warm up, stretching, music and visual feedback before competitions and training are necessary to improve athletic performance [2,[5][6][7][8][9][10]. Pre-exercise warm-up, a common technique, is defined as necessary to maximize the athlete's performance in a variety of sports and physical activities by changing the body's physiological mechanisms (muscle temperature, nerve conduction velocity, increased blood flow).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, Chtorou et al [2] found that power output increased in male sprinters during the 30-s Wingate Anaerobic Test (WAnT) after a 10-min warm-up with and without music. It has been reported in many exercises in the literature that methods such as warm up, stretching, music and visual feedback before competitions and training are necessary to improve athletic performance [2,[5][6][7][8][9][10]. Pre-exercise warm-up, a common technique, is defined as necessary to maximize the athlete's performance in a variety of sports and physical activities by changing the body's physiological mechanisms (muscle temperature, nerve conduction velocity, increased blood flow).…”
Section: Introductionmentioning
confidence: 99%
“…In music condition, participants applied to 15 minutes of warm up by listening to music (160 to 180 bpm) rather than just warm up (Edworthy & Waring, 2006;Karageorghis et al, 2008). Fifteen minutes warm up consisted of running for 5 minutes at a heart rate corresponding to 50% of the determined HRR and 10 minutes FWU exercises (stationary spider-man (30 s work -30 s rest), inchworm (30 s work -30 s rest), backward and forward lunge walks [2× (30 s work -30 s rest)], backpedal (30 s work -30 s rest), straight-leg skip (30 s work -30 s rest), heel-ups [2× (30 s work -30 s rest)] and high knee run [2× (30 s work -30 s rest)]) (Eken et al, 2022).…”
Section: D) High Rhythm Music Phase (Hmp);mentioning
confidence: 99%
“…However, in recent years, people with disabilities at the national and international levels have been using sports not only as a means of rehabilitation and socialization, but also to enhance performance (Cherif et al, 2022). Although the type of sports activities is important in increasing the level of performance (Hammami et al, 2019), the timing of the activity is also an important factor that affects the level of performance (Eken et al, 2022;Nişli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%